Safety and efficacy of canagliflozin in elderly patients with type 2 diabetes mellitus: a 1-year post-marketing surveillance in Japan. (1st February 2018) - Goda, Maki; Yamakura, Tomoko; Sasaki, Kazuyo; Tajima, Takumi; Ueno, Makoto
Abstract: Objective: To evaluate the safety and efficacy of canagliflozin in elderly patients with type 2 diabetes mellitus (T2DM) in clinical settings. Methods: The authors conducted a 1-year post-marketing surveillance (PMS) of canagliflozin in almost all the elderly patients (≥65 years old) with T2DM who began taking canagliflozin during the first 3 months after its launch in Japan. The main outcomes included the incidences of adverse drug reactions (ADRs), serious ADRs, and the changes of laboratory tests as well as efficacy variables. Results: An ADR was reported in 9.09% (125 of 1375 patients) in the safety analysis set. The main ADRs were dehydration, constipation, thirst, pollakiuria, dizziness, cystitis, eczema, pruritus, and rash. The incidence of serious ADRs was 1.02% (14 patients), which included urinary tract infection, dehydration, hypoglycemia, and cerebral infarction (two patients each). ADRs of special interest that had been reported in clinical trials of SGLT2 inhibitors, such as hypoglycemia, volume depletion-related events, genital/urinary tract infection, polyuria/pollakiuria, and ketone body increased were also observed in this PMS. The safety profiles were similar to the results of a previous clinical study of canagliflozin, and new safety concerns were not identified in this survey. The mean change in HbA1c was –0.77% after 12 months of treatment in the efficacy analysis set. Conclusion: In this PMS, the safety and efficacy profiles of canagliflozin in elderly patients with T2DM were obtained in the clinical settings in Japan and the drug was well tolerated and effective in improving glycemic control.